The "ableism'' behind Mental Health Professionals' Perceptions of Support - Hideki Muramatsu (Patient Experience Journal)
This paper presents the personal narrative of the author, an individual who has experienced personal and clinical recovery from mental health difficulties. Diagnosed with a mental disorder (NEUROTIC; ICD-10) during my university years, I endured cognitive dysfunction, panic disorder, derangement of ego, suicidal ideation, and depression. Despite these challenges, I have actively engaged in social skills training, supervised virtual reality content, led self-help groups, and published papers on my experiences. I will discuss my own experiences as an expert-by-experience and describe the tendencies of professional ableism consciousness that I encountered during my journey of recovery. Through the lens of my recovery journey, I describe the difference between professionals with a strong ableism mindset and those with a weak ableism mindset. To mitigate ableism, mental health professionals must confront their own biases, as seen in training analyses. They also require an enhanced understanding of recovery and a shift toward recovery orientation. My story underscores the importance of a cautious and humble approach that does not evaluate human superiority or inferiority in the context of ableism. I hope that the readers of this paper will be inspired to think about professional ableism and move in the direction of shaping public opinion toward a decrease in ableism.